PENGARUH TEKNOLOGI INFORMASI BERBASIS ANDROID (SMARTPHONE) DALAM PENDIDIKAN INDUSTRY 4.0 - Destiana, Destiana (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Information Technology is a term to define everything or technological equipment that is able to make it easy for someone to make, change, store or even disseminate information to each other one of which is android where the function of Android is a communication tool such as smartphones where this smartphone is one of the most sophisticated science and technology products today. This is because mobile phones are able to access information in all corners of the world in a relatively short time and almost simultaneously and relatively inexpensive costs. Mobile phones can have a positive and negative impact on teachers. Possible efforts that can be applied to the negative impacts caused by mobile phones include the professionalism of teachers in use, in order to use mobile phones with smartphones at the right time. Even teachers can use smartphones as learning facilities and the most important information center and as a media tool.